Shellfish consumption preferences in an oceanic archipelago - Sousa, Ricardo; Gaspar, Madalena; Lucas, Jorge; Freitas, Mafalda; Ideia, Pedro (Frontiers in Marine Science, 2023)
A survey on shellfish consumption preferences was conducted in the Eastern Atlantic archipelago of Madeira. A total of 402 valid questionnaires were collected from locals older than 15 years old. Gender, age, highest education level, work status and salary were considered in the sample composition. Participants were inquired about frequency, amount and risks associated with consumption, as well as concerns regarding the freshness of seafood. Shellfish appears to be consumed less than once a week, and 79.1% of these consumers prefer limpets. GLM analysis showed that total salary amount was the demographic variable which most affects seafood consumption. The results indicated that the majority of the respondents consume limpets less than once a week, in an amount that varies between a quarter and a half dose. With regard to health concerns, most respondents are conscious of the importance of products’ freshness and approximately half of them are aware of the existence of risks associated with consumption. In general, the awareness about freshness and possible risks of consumption is dependent on the level of education. Limpets are preferably consumed during summer, both grilled and cooked, respectively. The present study provides preliminary information on shellfish consumption trend in the archipelago of Madeira. Raising the awareness of seafood consumers in line with a health surveillance network in preparation in Macaronesia could be an important tool for spreading information related to the risks associated to its consumption.